How scholars prioritize the competing values of conservation and sustainability - Vucetich, JA; Bruskotter, JT; van Eeden, LM; Macdonald, EA (Elsevier, 2021)
Aspirations for human-nature relationships involve values that are widely embraced, yet often compete with one another. As such, there is need to understand how individuals prioritize competing values pertaining to human-nature relationships. To quantify individuals' affinity for those conservation priorities, we developed a survey instrument asking individuals to respond to forced trade-offs between pairs of competing values. Forced trade-offs are relevant to the extent one perceives that limited resources preclude satisfying all the values and interests at stake in human-nature relationships. We administered this survey to 459 scholars of conservation and sustainability. Factor analysis supports the acknowledgement of five conservation priorities. Two prioritizations lean toward non-anthropocentrism and are aptly labelled, orthodox conservation and organism-oriented conservation. Three prioritizations lean toward anthropocentrism and are aptly labelled, future generations, present-day fairness, and neoliberalism. In spite of the forced trade-offs, most individuals expressed strong affinity for multiple priorities. That result suggests that polarizing discourse about controversies in conservation is likely representative of a small portion of people. Also, specific cases in conservation involving competing values are often adjudicated by case-specific context, as opposed to the one priority most appreciated by an individual. The results are consistent with psychological evidence indicating that moral judgments (about human-nature relationships) are typically intuitive and subsequently affirmed by moral reasoning. Results also indicate that the five conservation priorities are not readily reducible to other basic values (utilitarianism, social justice).